Preoperative Embolization of the Splenic and Left Gastric Arteries does not Seem to Decrease the Rate of Anastomotic Leaks after Esophagogastrectomy (Global Journal of Medical Research, 2016)
Introduction: Embolization of the gastric and splenic artery is performed to improve blood flow to the constructed gastric tube during esophagectomy and thus reduce the rate of anastomotic leaks for this type of surgery. Patients and Methods: This is a retrospective, comparative study conducted from 2003 to 2013 of 32 patients undergoing preoperative embolization versus 102 patients not undergoing embolization to assess the impact of this technique on the rate of anastomotic leakage. The variables considered were age, gender, comorbidities, preoperative histopathology, location of the tumor, type of neoadjuvant therapy (if appropriate), type of surgery and type of anastomosis. Results: Patients had similar epidemiological and pathologic characteristics, except for the neoadjuvant treatment received. Of the 32 patients having embolization, 28 (87.5%) received chemoradiotherapy preoperatively, whereas only 52 of the 102 (50%) patients not having embolization received this therapy (p=0.0001). Of the 32 patients undergoing embolization, 14 (43.75%) developped an anastomotic leak versus 33 (32.35%) of the 102 patients not having embolization. No statistically significant differences were observed (p=0.289). Conclusions: Although ischemic conditioning of the constructed gastric tube by embolization of the left gastric artery and splenic artery prior to esophagectomy is a safe approach unrelated with morbidity, we could not demonstrate that it reduces the rate of anastomotic leaks.